Bahamian hutia (Geocapromys ingrahami) in the Lucayan Realm: Pre-Columbian Exploitation and Translocation. (3rd April 2019) - LeFebvre, Michelle J.; DuChemin, Geoffrey; deFrance, Susan D.; Keegan, William F.; Walczesky, Kristen
ABSTRACT: Bahamian hutia ( Geocapromys ingrahami ) are endemic to The Bahamas. The skeletal remains of this species have been recovered from multiple Lucayan-associated archaeological sites in the region, suggesting that it was an important source of human food. This study explores the role of pre-Columbian indigenous peoples in the geographic distribution of Bahamian hutias, and the possibility of intentional management of the animal. We provide an overview of archaeological occurrences of Bahamian hutia and present new skeletal morphometric data comparing modern museum-curated Bahamian hutia specimens with archaeological specimens from the Palmetto Junction site on Providenciales located in the Turks and Caicos Islands. Bahamian hutia do not exist in the fossil record in the Turks and Caicos, indicating their translocation to the islands by humans. Our data show that individual hutia at Palmetto Junction were larger than modern specimens. This size variation may be due to anthropogenic influence; however, there is limited information regarding either natural size variation within the species or environmental factors possibly influencing size. Continued research on anthropogenic influences related to Bahamian hutia populations, coupled with isotopic studies of the Bahamian hutia diet, may further elucidate the practice of pre-Columbian management of the species.